1980
DOI: 10.1007/bf00237543
|View full text |Cite
|
Sign up to set email alerts
|

Auditory evoked transient and sustained magnetic fields of the human brain localization of neural generators

Abstract: A long auditory stimulus elicits a magnetic evoked response in the human brain, consisting of transient deflections followed by a sustained response. The distributions of the magnetic fields indicate that the auditory evoked transient response at a latency of 100 ms as well as the auditory sustained response are generated at and around the primary auditory cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(135 citation statements)
references
References 17 publications
10
122
0
3
Order By: Relevance
“…When the EEG is recorded with a nose reference, the fronto-centrally peaking negative waveform often shows a polarity inversion at mastoid sites (Vaughan & Ritter, 1970), suggesting that one of the subcomponents originates from a supratemporal generator structure. Indeed, event-related magnetic field (ERF) counterparts of N1 (the N1m) recorded with MEG closely correspond to fields generated by tangentially oriented dipoles located in the supratemporal auditory cortex (see Elberling, Bak, Kofoed, Lebech, & Saermark, 1980;Hari, Aittoniemi, Järvinen, Katila, & Varpula, 1980).…”
Section: Typical Findings In the Contingent Paradigmmentioning
confidence: 89%
“…When the EEG is recorded with a nose reference, the fronto-centrally peaking negative waveform often shows a polarity inversion at mastoid sites (Vaughan & Ritter, 1970), suggesting that one of the subcomponents originates from a supratemporal generator structure. Indeed, event-related magnetic field (ERF) counterparts of N1 (the N1m) recorded with MEG closely correspond to fields generated by tangentially oriented dipoles located in the supratemporal auditory cortex (see Elberling, Bak, Kofoed, Lebech, & Saermark, 1980;Hari, Aittoniemi, Järvinen, Katila, & Varpula, 1980).…”
Section: Typical Findings In the Contingent Paradigmmentioning
confidence: 89%
“…Thus, N1 is a fronto-centrally component with a peak latency of 100 ms after stimulus onset generated bilaterally mainly in the auditory cortices. Its magnetic equivalent (N1 m/N100 m; Elberling et al 1980;Hari et al 1980) originates deep within the Sylvian fissure in tonotopically organized areas (Yamamoto et al 1988;Cansino et al 1994), but also comprises secondary areas such as Heschl's gyrus, STG and planum temporale providing the major source (Papanicolaou et al 1990;Pantev et al 1995;Jääskeläinen et al 2004;Inui et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Using an oddball procedure, i.e., frequent standard stimuli and infrequent deviant stimuli, the amplitude of the MMN is known to increase with decreasing physical similarity between deviant and standard. However, while this relationship between physical similarity and MMN amplitude has proven valid for sinusoidal tones [Hari et al, 1980;Näätänen et al, 1978;Sams et al, 1985] and complex tones [Näätänen et al, 1993;Vihla et al, 2000], it has been shown that the mismatch negativity in response to deviating speech sounds is dependent on languagespecific long-term memory traces. Non-prototypical speech sounds in a given language, i.e., foreign phonemes, evoke an MMN that is weaker than the one evoked by the prototypical phonemes [Näätänen et al, 1997;Winkler et al, 1999].…”
Section: Introductionmentioning
confidence: 99%